Fatigue of low alloyed carbon steels in the HCF/VHCF-regimes - Bachmann, Jonas; Göken, Mathias; Höppel, Heinz Werner (Fatigue of Materials at Very High Numbers of Loading Cycles, 2018)
The fatigue behaviour and damage evolution in body centered cubic low alloyed steels in the high cycle and very high cycle fatigue regimes (HCF/VHCF) were in focus of this work. For this purpose, the steels C15E, C45E and C60E, with different ferritic-pearlitic microstructures were investigated. Due to the different carbon contents the ratio of ferrite to pearlite decreased from C15E to C60E. C15E mainly consist of ferrite grains. The ferrite grains deform plastically under cyclic loading. With decreasing stress amplitudes plastic deformation becomes more and more localized in particular ferrite grains. During further cyclic loading plastic deformation accumulates in those grains and finally leads to crack initiation and fatigue failure. The accumulation of irreversible plastic deformation in the ferrite grains and the strength of microstructural barriers in the vicinity of the plastically deformed grains are mainly determining the total fatigue life. In order to assess quantitatively the contribution of irreversible plastic deformation a new method was developed. By determining the dissipated energy per fatigue cycle, which was derived from the power input of the ultrasonic fatigue machine, it is possible to account for the amount of irreversibility during one loading pulse. Based on these results a prediction of the fatigue life can be made at a very early stage of the fatigue experiment. It also allows distinguishing very early whether the specimen will become a runout or if it will fail at a given amplitude. It also turned out that the interaction of localized plastic deformation with microstructural barriers in the direct vicinity is the key for understanding the occurrence of late fatigue failure. If specimens showed macroscopic crack growth and fatigue failure, critical cracks always initiated at interfaces. On the other hand, runout specimens showed some crack nuclei, but they were not able to overcome the next microstructural barrier.<br

Quality control of polymer solar modules by lock-in thermography - Hoppe, Harald; Bachmann, Jonas; Muhsin, Burhan; Druee, Karl-Heinz; Riedel, Ingo; Gobsch, Gerhard; Buerhop-Lutz, Claudia; Brabec, Christoph; Dyakonov, Vladimir (Journal of Applied Physics, 2010)
We have characterized lateral imperfections of photovoltaic modules based on solution processed polymer-fullerene semiconductor blends by means of lock-in thermography (LIT). The active layer of the solar cell modules is based on the heterogeneous organic semiconductor system poly(3-hexylthiophene):phenyl-C -butyric acid methyl ester and the power conversion efficiency of the modules reached nearly 2% under irradiation of an AM 1.5 solar simulator. Applying highly sensitive LIT allowed us to detect several kinds of laterally distributed defects originating from imperfections in the respective functional layers as well as in the quality of encapsulation. We show that LIT is a powerful method for the quality control of large area polymer solar cells and modules, enabling fast feedback for optimization of production parameters. © 2010 American Institute of Physics.

Time-resolved imaging of Œrsted field induced magnetization dynamics in cylindrical magnetic nanowires - Schöbitz, M.; Finizio, S.; De Riz, A.; Hurst, J.; Thirion, C.; Gusakova, D.; Toussaint, J. C.; Bachmann, Jonas; Raabe, J.; Fruchart, O. (Applied Physics Letters, 2021)
Recent studies in three-dimensional spintronics propose that the Œrsted field plays a significant role in cylindrical nanowires. However, there is no direct report on its impact on magnetic textures. Here, we use time-resolved scanning transmission x-ray microscopy to image the dynamic response of magnetization in cylindrical Co30Ni70 nanowires subjected to nanosecond Œrsted field pulses. We observe the tilting of longitudinally magnetized domains toward the azimuthal Œrsted field direction and create a robust model to reproduce the differential magnetic contrasts and extract the angle of tilt. Furthermore, we report the compression and expansion, or breathing, of a Bloch-point domain wall that occurs when weak pulses with opposite signs are applied. We expect that this work lays the foundation for and provides an incentive to further studying complex and fascinating magnetization dynamics in nanowires, especially the predicted ultra-fast domain wall motion and associated spin wave emissions.
CRIS-Team Scopus Importer:2021-05-14